Phylogenomics of the tetraploid Hawaiian lobeliads: Implications for their origin, dispersal history, and adaptive radiation - Jeffrey P. Rose; Bing Li; Margaret J. Sporck-Koehler; Elizabeth A. Stacy; Kenneth R. Wood; Emily Moriarty Lemmon; Alan R. Lemmon; Cécile Ané; Kenneth J. Sytsma; Thomas J. Givnish (Proceedings of the National Academy of Sciences, 2025)
Hawaiian lobeliads exhibit extensive adaptive radiations and are considered the largest plant clade (143 species) endemic to any oceanic archipelago. Rapid insular radiations are prone to reticulate evolution, yet detecting hybridization is often limited by inadequate sampling of taxa or independent loci. We analyzed 633 nuclear loci (including tetraploid duplications) and whole plastomes for 89% of extant species to derive phylogenies for the Hawaiian lobeliads. Nuclear data provide strong support for nine major clades in both likelihood and ASTRAL analyses. All genera/sections are monophyletic except Clermontia and Cyanea . Nuclear and plastome phylogenies conflict on short, deep branches; the nuclear tree resolves a fleshy-fruited clade of Hawaiian Clermontia/Cyanea-Brighamia/Delissea , sister to Polynesian Sclerotheca , with both sister to a capsular-fruited Hawaiian clade. Incomplete lineage sorting in a rapid radiation starting 8.5–11.3 Ma is sufficient to explain uncertainty and cytonuclear discordance along the backbone. Sequence data support reticulation within Clermontia and especially Cyanea . Nuclear data identify 42 interisland dispersal events: 89% accord with the strict progression rule, involving movement to the next younger island in the hotspot chain, consistent with theory. Plastid data overestimate such events by 17%. Cyanea and Clermontia have undergone parallel adaptive radiations in elevational distribution and flower length on all major islands, with multiple founders and some interisland differences. Hawaiian lobeliad diversification was driven by an early intergeneric divergence in habitat, followed by parallel adaptive radiation and ecological speciation within Clermontia/Cyanea , combined with widespread single-island endemism, frequent interisland dispersal, and occasional hybridization.